Self-reporting visible light-induced polymer chain collapse. Issue 33 (25th July 2019) - Offenloch, Janin T.; Blasco, Eva; Bastian, Simon; Barner-Kowollik, Christopher; Mutlu, Hatice
Abstract : We introduce a facile photoinduced self-reporting crosslinking methodology for the compaction of polymer chains in highly diluted solution. Abstract : We introduce a facile photoinduced self-reporting crosslinking methodology for the compaction of polymer chains in highly diluted solution. The chain compaction, which is readily monitored via the change in optical properties due to the release of the chromophore, is achieved via mild visible light irradiation (430–435 nm) of statistically distributed pyrene-substituted oxime ester derivatives. In-depth characterization via size exclusion chromatography (SEC), UV/Vis and fluorescence spectroscopy, as well as NMR measurements including diffusion ordered spectroscopy (DOSY), reveals an efficient system, which may serve as a blueprint for reading out the state of SCNPs in more complex scenarios.